Policy Formulation of National Security - Jandaeng, Burachat; Phosing, Assoc. Prof. Dr. Phakdee; Kenaphoom, Assoc. Prof. Dr.Sanya (Journal for Developing the Social and Community, 2018)
National Security Policy As a policy about which Escort sovereignty of national unity. Territorial integrity And the Institute of National As well as protecting Protection of public and national interests on the part of the prescription form of national security policy. The Office of the National Security Council will be responsible for formulating policy on national security. The Prime Minister as Chairman of the National Security Council to approve a policy for current national security policy of Thailand, he stressed the importance of maintaining stability in the country and preventing new forms of threats. Particularly care to social awareness. And can adapt to crisis during the transitional political crisis can prevent the risk of violence as much as possible. The nation has managed to coexist peacefully with them. Although there are differing opinions to create fairness and justice in society as well as the moral and the lifestyle of sufficiency economy is the goodness of Thailand back. Everyone sees the value of peace. National reconciliation and the power to build a solid foundation to prepare them to face the climate change aspects.